Precipitated Silica by Precipitation Process of The Sodium Silicate Solution with Carbon Dioxide Gas (Co2) on Fixed Bed Column - S. Muljani; R. Dewati; Suprihatin; K. Sumada (Future Science)
Precipitated silica is a silica product produced by a precipitation process, this silica product contains silica, white color, very porous and nanomaterial. This precipitate silica is required to support various types of industrial operations such as vehicle, rubber, cosmetics, electronics, agriculture and other industries. The precipitated silica is produced through two stages of the process: firstly is silica extraction process with the base solution and the secondly is precipitation processes of silica solution with various types of acids such as hydrochloric acid (HCl), sulfuric acid (H2SO4), acetic acid (CH3COOH) and other acids. In this study, the source of silica was obtained from bagasse ash waste of sugar industry, the base solution as a solvent was sodium hydroxide (NaOH) 2 N and the precipitate process was carried out by using carbon dioxide gas (CO2) and the precipitation process was carried out on a fixed bed column. In this study we studied the effect of silica concentration on the inlet feed and the high of the fixed bed on the quality of the precipitated silica product. Based on the results of this study, the quality of precipitated silica produced as follows: 95-98% silica content, weight loss due to temperature heating 105 C: 4 – 5 %, acidity (pH of slurry 5%) : 6.8-7,1, and surface area (BET): 175 m2/gram. The best conditions in this study were 30 cm high of fixed bed, and concentration of silica feed: 0,33% weight and acidity (pH) precipitation 7,1.